The development of finite element model for Malaysian Female Anthropometric Dummy - Tam, Lina (2015)
In recent years, dummy development for crash test have grown rapidly to decrease the fatalities during crash. These dummies are generated based on anthropometric database consisting of several percentile. Anthropometric data is very important in terms of ergonomics to specify the physical dimensions for product design and dynamic behavior for user safety. The development of dummy models starts from rigid body models to deformable models which is then adopted into finite element models for more accurate and detailed results in doing analysis. Using the numerical method (FEM) to evaluate crash test has increase the cost saving and accuracy in crash analysis. An average anthropometric of 100 Malaysian females with 59 anthropometric data is modeled using Solidworks 2010. The parameters of boundary conditions for the model are conducted in the preprocessor called GiD, before the input file from GiD is run using an explicit finite element program suite called Impact. The dummy model is set in sitting position and crushed with a chair at velocity 15.3ms−1 from behind. The deformation which includes as displacements, velocity and acceleration are presented in this research. The results show that the head experienced the bounce and highest displacement. This model can be further complemented for the family of Malaysian Anthropometric Test Dummy in computational test dummies to improve safety for local passengers.